Collagen microencapsulation recapitulates mesenchymal condensation and potentiates chondrogenesis of human mesenchymal stem cells – A matrix-driven in vitro model of early skeletogenesis. (August 2019) - Li, Yuk Yin; Lam, Kwok Lim; Chen, Abigail Dee; Zhang, Wei; Chan, Barbara Pui
Abstract: Mesenchymal condensation is a critical transitional stage that precedes cartilage or bone formation. A microencapsulation technique was previously established to entrap mesenchymal stem cells (MSC) in nanofibrous collagen meshwork. We hypothesize that collagen microencapsulation of MSCs mimics the mesenchymal cell condensation process. Specifically, human MSCs at different concentrations were microencapsulated in collagen for different time points before evaluation for early skeletogenesis markers. A transient upregulation of mesenchymal condensation markers including peanut agglutinin, fibronectin, integrins α5 and αv, an enhanced nuclear localization of SOX9 and binding interactions with COL2A1, and other changes in chondrogenic, hypertropic and osteogenic marker were demonstrated. Collagen microencapsulation upregulated both the chondrogenic and the osteogenic transcription factors and the encapsulated hMSCs hold the potential to differentiate towards both chondrogenic and osteogenic lineages. We also hypothesize that collagen microencapsulation potentiates MSC chondrogenesis. Particularly, chondrogenic differentiation of hMSCs were induced at different time post-encapsulation before evaluation for chondrogenesis outcomes. Sustained SOX9, ACAN and COL2A1 expression were noted and the timing to induce supplement chondro-inductive factors matters. This study reports an extracellular matrix-based in vitro model of mesenchymal condensation, an early stage in skeletogenesis, contributing to rationalizing development-inspired tissue engineering.